Machine utilization in a motor cycle rubber parts manufacturing company - Suchart Tachaplalert; Pastijn, Hugo; Pandey, Indra M.; Bohez, Erik L.J.; Kuehn, Wolfgang (Bangkok : Asian Institute of Technology, 1994)
Motor cycle manufacturing is becoming a large and growing industry, especially in Thailand and the south-east Asian countries such as Laos, Vietnam and Cambodia. Almost I 00% of the market share in this region belong to the Japanese manufacturers and that is why the motor cycle assemblers and parts manufacturers in Thailand has to develope to the Japanese production philosophy, the Just-In-Time system. For the motor cycle rubber parts manufacturing system, the orders from the assemblers are usually in small but frequent lot sizes and the objective of the company is to meet the due dates.The problem of the company under study is to find out whether the existing system can cope with future increase in demand. The system is simulated using the SIMPLE++ simulation package. To increase productivity, the concept of machine utilization is used to investigate the bottleneck of the system. The results obtained from simulattion model agree with the existing system that the 20" press machines are the bottleneck of the system. Alternative plans developed by the company and the author are tested on SIMPLE++ and it is found that Plan 1 (redesigning of molds) is a better choice in term of machine utilization, overall output and meeting the increasing market demand and customer's service.
A thesis submitted m a partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Motorcycle supplies industry